The Influence of Financial Distress, Debt Default, Company Growth, and Company Size on The Going Concern Audit Opinion - Hidayatul Nikmah; Atwal Arifin (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze whether financial distress, debt default, company size, and company growth influence the going concern audit opinion. The population of this study consists of 56 companies in the material sector listed on the Indonesia Stock Exchange during the period 2020-2022 that meet all the specified criteria. Secondary data from www.idx.co.id and relevant company websites were used for this research. The sampling technique employed was purposive sampling, resulting in a total sample size of 159 companies after adjustment with the purposive sampling criteria. Data collection was conducted through documentation methods using logistic regression analysis technique. The results of this study indicate that company growth significantly influences the internal going concern audit opinion in the material sector listed on the Indonesia Stock Exchange during the period 2020-2022, while financial distress, debt default, and company size do not affect the internal going concern audit opinion in the material sector listed on the Indonesia Stock Exchange during the period 2020-2022.